Management and coping strategies for children with chronic kidney diseases during major public health emergencies: reflections on the outbreak of novel coronavirus pneumonia - WANG Mo; YANG Hai-ping; CHEN Xue-lan; LI Qiu; ZHANG Ai-hua (Linchuang shenzangbing zazhi)
The 2019 novel coronavirus(2019-nCoV) infection has covered the whole country since mid-December 2019. Tens of thousands cases have been confirmed in various provinces, cities and overseas countries. The infection situation is very serious, all provinces and cities have launched the first-level response to major public health emergencies. The epidemiological investigation has indicated that the general population is susceptible to 2019-nCoV, and the children with chronic kidney disease(CKD) are at high risk. The management of children with CKD characterized by chronic diseases has shown a series of problems, such as how to prevent and control the epidemic situation of children with CKD, how to ensure the continuation of treatment, etc. Based on the outbreak of 2019-nCoV pneumonia, this article puts forward some suggestions on the coping strategies and system construction for management of children with CKD during major public health emergencies.